2010
DOI: 10.1007/s11368-010-0280-9
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic, cadmium, and lead pollution and uptake by rice (Oryza sativa L.) grown in greenhouse

Abstract: Purpose Hunan province is well-known for its extensive base-metal extraction and smelting industries. However, the legacies of excavation operations, transportation, and selective smelting activities within Hunan have resulted in the generation of large quantities of mine wastes, which will become the sources of metal contamination in the environment. Thus, there is an increasingly important health issue underlying the study of arable land pollution and transfer of As, Cd, and Pb in the paddy soil-rice system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 24 publications
(27 reference statements)
1
15
0
Order By: Relevance
“…The high levels of Cd, Zn, Pb, and As contained in iron plaque supports the general consensus that iron plaque has a high adsorption capacity for metal(loid)s (Liu et al 2006;Lei et al 2011). However, iron plaque sequestered less Cd and Pb after BCs amendment though Zn and As concentrations in iron plaque were not significantly influenced (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…The high levels of Cd, Zn, Pb, and As contained in iron plaque supports the general consensus that iron plaque has a high adsorption capacity for metal(loid)s (Liu et al 2006;Lei et al 2011). However, iron plaque sequestered less Cd and Pb after BCs amendment though Zn and As concentrations in iron plaque were not significantly influenced (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…However, this extra iron plaque sequestered more Pb but not Cd, Zn and As (Fig. 2), despite the general consensus that iron plaque has a high adsorption capacity for all metals (Liu et al, 2008;Lei et al, 2011). For Cd and Zn, this is likely attributable to their C pw decreasing after biochar additions (Fig.…”
Section: Modelmentioning
confidence: 92%
“…This iron plaque exhibits a high capacity to sequestrate certain metals. The proportion of As, Cd, and Pb distributed in iron plaque on rice root surface could reach 88%, 43% and 33% respectively (Lei et al, 2011). The presence of iron plaque on root surfaces has been reported to reduce the uptake of metals by plants because of the high adsorption capacity of its iron hydroxide functional groups (Greipsson and Crowder, 1992;Batty et al, 2000;Liu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2004) reported that the As sequestrated by iron plaques (i.e., dithionite-citrate-bicarbonate [DCB] extractable As) on root surfaces was about 75-89 % of the total rice plant As and suggested that iron plaques may act as a barrier to prevent As absorption and translocation by rice plants. More recently, Lei et al (2011) showed that As, Cd, and Pb accumulations in iron plaques on the root surface relative to rice plant total accumulation reached about 88, 44, and 34 %, respectively. It has been suggested that iron plaques on rice roots could provide a barrier to soil Pb stress and increase sequestration of Pb on the rice root surface (Liu et al 2011), and this has been further supported by Zheng et al (2012) who found that iron plaques sequestered much more Pb than Cd, Zn, and As.…”
Section: Introductionmentioning
confidence: 99%